Colorism attitudes and use of skin lightening agents in the United States - Karishma Daftary, MD; Sneha Poondru, BA; Nina Patel, MS; Maxwell Shramuk, MS; Lutfiyya Muhammad, PhD; Roopal V. Kundu, MD (Wolters Kluwer, 2023)
Background:. Skin lightening (SL) is a practice involving the use of chemicals to lighten the skin that is more common among skin of color (SOC) individuals, particularly women, and can lead to adverse health consequences. Objective:. In this study, we examine SL habits, including both general lightening and lightening for the treatment of a skin condition, among SOC individuals in the United States and the role of colorism in motivating these behaviors. Methods:. A cross-sectional survey was administered to SOC individuals through ResearchMatch, an online national health registry. Demographics, rates of SL, SL habits, and perceived colorism among SL users and nonusers were collected and analyzed with χ2, Fisher's exact, Analysis of variance (ANOVA), Spearman correlation, and t tests. Results:. A total of 455 participants completed the survey. Ninety-seven participants (21.3%) reported using SL agents: 73.2% (71/97) used SL agents for the treatment of a skin condition and 26.8% (26/97) used the products for general SL. Only 22.6% (22/97) of SL users consulted a medical provider before using the products. Forty-four participants (45.4%) were unaware of their SL product ingredients, and 35.1% (34/97) reported using hydroquinone-based products. Composite colorism scores were significantly higher in SL users than nonusers (20.03 vs 18.20; P < .001). Limitations:. This study used self-reported racial/ethnic groups to characterize those with SOC rather than assessing actual skin tones of participants, which could have led to variability. Conclusion:. SL among SOC individuals is prevalent in the U.S. and poses a health risk, as many SL users are unaware of product ingredients, do not consult a medical provider before use, and have access to potentially unsafe formulations. Dermatologists should address skin tone and pigmentary concerns with their SOC patients.